Extenics and innovation methods : proceedings of the International Symposium on Extenics and Innovation Methods, Beijing, P.R. China, 16-18 August 2013 /: proceedings of the International Symposium on Extenics and Innovation Methods, Beijing, P.R. China, 16-18 August 2013. ([2013]) - Unknown
No abstract available